1999
DOI: 10.1108/01443579910260883
|View full text |Cite
|
Sign up to set email alerts
|

Virtuous and vicious cycles on the road towards international supply chain management

Abstract: An increasing number of companies claim to pursue international supply chain management (ISCM), but the empirical evidence of successful implementation programs is still scarce. This paper aims to contribute to theory-building in this area by presenting an exploratory causal model of goals, barriers, and enablers on the road towards effective ISCM. The model was established in a workshop with a panel of content matter experts. The results point at a disturbingly gloomy picture of vicious cycles frustrating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
144
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 207 publications
(161 citation statements)
references
References 21 publications
0
144
0
6
Order By: Relevance
“…As pointed out by Tan et al (1999Tan et al ( , 2002, as well as Akkermans et al (1999), implement a change in culture among the employees in the firms that make up the chain, the aim being to seek a more participatory style of management by introducing into their activities the concept of continuous improvement and the need to be customer-oriented.…”
Section: Concept Of Supply Chain Integrationmentioning
confidence: 99%
“…As pointed out by Tan et al (1999Tan et al ( , 2002, as well as Akkermans et al (1999), implement a change in culture among the employees in the firms that make up the chain, the aim being to seek a more participatory style of management by introducing into their activities the concept of continuous improvement and the need to be customer-oriented.…”
Section: Concept Of Supply Chain Integrationmentioning
confidence: 99%
“…The Delphi technique lends itself especially well to exploratory theorybuilding (Meredith et al 1993, Neely 1993 on complex, interdisciplinary issues, often involving a number of new or future trends (e.g. Klassen and Whybark 1994, Akkermans et al 1999).…”
Section: 1 a D E L P H I S T U D Y R E S E A R C H D E S I G Nmentioning
confidence: 99%
“…However, Msimangira's (1993) study on using JIT in developing countries revealed that there are many problems which affect the usage of JIT, such as international delivery delays, inadequate transportation infrastructure, unreliable product demand forecasts, and financial constraints. Akkermans et al (1999) propose that it is possible to implement effective international supply chain management strategies by promoting cross-functional careers and by actively responding to customer needs, and the idea is supported by Oliva & Watson (2011). In addition, Prasad, et al (2001) argue that supply chains learn and adapt to the dynamic global environment.…”
Section: Global Supply Chainmentioning
confidence: 99%